Cymbella ectorii sp. nov. (Cymbellales, Gomphonemataceae) from a Miño River (NW, Spain) - Cid-Rodríguez, María; Blanco, Saúl; Tascón-Peña, Osvaldo; Delgado, Cristina (Phytotaxa, 2025)
Cymbella ectorii sp. nov. is a new freshwater diatom described from phytobenthos samples of Miño River (Galicia, NW of Iberian Peninsula). This new diatom is illustrated and discussed based on different samples collected in July-August 2015 in Miño River as it passes through the city of Ourense and was found four years later (2019) at the same sites. Cymbella ectorii sp. nov. is placed in the genus Cymbella due to shared features such as asymmetry about the apical axis, deflection of the external terminal raphe fissures towards the dorsal margin, and the presence of apical pore fields and stigmata. This taxon was compared with other Cymbella taxa, and its morphological features are documented through light and scanning electron micrographs. Cymbella ectorii sp. nov. is characterized by solitary cells, moderately dorsiventral and broadly lanceolate valves, a distinctly convex dorsal margin and a moderately convex ventral margin. Ends are not protracted but are slightly subrostrate and bluntly rounded. This taxon may be confused with other taxa such as Cymbella tumidula var. tumidula, C. tumidula var. procera, C. tropica, C. affinis, C. turgidula and Cymbopleura heilprinensis in terms of length, stria density and outline. Cymbella ectorii sp. nov. was found in freshwater environments with high dissolved oxygen concentrations, low conductivity, neutral to slightly alkaline pH and low nitrate concentrations.